Maternal sensitivity and adrenocortical functioning across infancy and toddlerhood: Physiological adaptation to context?. (11th April 2016) - Berry, Daniel; Blair, Clancy; Willoughby, Michael; Granger, Douglas A.; Mills-Koonce, W. Roger; ,
Abstract: Theory suggests that early experiences may calibrate the "threshold activity" of the hypothalamus–pituitary–adrenal axis in childhood. Particularly challenging or particularly supportive environments are posited to manifest in heightened physiological sensitivity to context. Using longitudinal data from the Family Life Project ( N = 1, 292), we tested whether links between maternal sensitivity and hypothalamus–pituitary–adrenal axis activity aligned with these predictions. Specifically, we tested whether the magnitude of the within-person relation between maternal sensitivity and children's cortisol levels, a proxy for physiological sensitivity to context, was especially pronounced for children who typically experienced particularly low or high levels of maternal sensitivity over time. Our results were consistent with these hypotheses. Between children, lower levels of mean maternal sensitivity (7–24 months) were associated with higher mean cortisol levels across this period (measured as a basal sample collected at each visit). However, the magnitude and direction of the within-person relation was contingent on children's average levels of maternal sensitivity over time. Increases in maternal sensitivity were associated with contemporaneous cortisol decreases for children with typically low-sensitive mothers, whereas sensitivity increases were associated with cortisol increases for children with typically high-sensitive mothers. No within-child effects were evident at moderate levels of maternal sensitivity.